Current Practice of State-of-the-Art Coronary Revascularization in Patients with Heart Failure - Rayol,Sérgio Costa (2019)
Abstract The best treatment for patients with ischemic heart failure (HF) is still on debate. There is growing evidence that coronary artery bypass graft (CABG) benefits these patients. The current recommendations for revascularization in this context are that CABG is reasonable when it comes to decreasing morbidity and mortality rates for patients with severe left ventricular dysfunction (ejection fraction <35%), and significant coronary artery disease (CAD) and should be considered in patients with operable coronary anatomy, regardless whether or not there is a viable myocardium (class IIb). Percutaneous coronary intervention (PCI) does not have enough data to allow the panels to reach a conclusion. The Korean Acute Heart Failure registry (KorAHF) had its data released recently, showing that patients with acute HF who underwent CABG had lower death rates, more complete revascularization and less adverse outcomes compared with patients treated with PCI. Recent ESC/EACTS guidelines on myocardial revascularization clearly recommended CABG as the first choice of revascularization strategy in patients with multivessel disease and acceptable surgical risk to improve prognosis in this scenario of left ventricular dysfunction. However, a high peri-procedural risk must be compared with the benefit of late mortality, and pros and cons of each strategy (either PCI or CABG) must be weighed in the decision-making process. Spurred on by the publication of the above-mentioned article and the release of new guidelines, we went on to write an overview of the current practice of state-of-the-art coronary revascularization options in patients with HF.